Normative and appearance performance-approach goal structures: Two-level factor structure and external linkages. Issue 1 (2nd January 2022) - Bardach, Lisa; Yanagida, Takuya; Klassen, Robert M.; Lüftenegger, Marko
Abstract: While personal performance-approach goals (PAp goals) have already been successfully bifurcated into normative and appearance PAp goals, the same distinction has not yet been applied to performance-approach goal structures (PAp goal structures). The present study therefore aimed to (a) test the factorial two-level structure of PAp goal structures to establish whether a distinction between normative and appearance components is empirically supported, and (b) explore relations to achievement and approach-oriented achievement goals (mastery-approach goals, normative and appearance personal PAp goals). This study relied on a sample of 1, 004 secondary school students (53.38% females, 49 classes). Results from multilevel confirmatory factor analyses revealed that a model with two separate normative and appearance PAp goal structure factors on the individual student level, and one overall PAp goal structure factor on the classroom level fit the data best. On the individual student level, normative PAp goal structures positively predicted achievement, whereas appearance PAp goal structures negatively predicted achievement. Each PAp goal structure type showed the strongest relation to the matching personal PAp goal, but no relations to mastery-approach goals were found. On the classroom level, the high associations between the overall PAp goal structure and personal PAp goals raised concerns on their empirical distinctiveness.